Pattern of Uterine and Cervical Lesions Marked on Histopathological Examination of Hysterectomy Specimens - Henna Khalid, Mariam Riaz, Momina Khadija Abbasi, Bushra Adeel, Sadia Shoukat, Reema Fateh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In Gynecology, most of the knowledge circles around the female reproductive tract and uterus has been a vital organ playing central role in female reproductive life cycle both in terms of menstrual and ostereous cycles. Uterus is subjected to both mechanical and hormonal stresses so uterine pathologies and diseases are the most common pathologies marked in female reproductive systems. These pathologies range from benign uterine pathology to malignancy in many cases. Most of the uterine and cervical pathologies are diagnosed after hysterectomy on histopathological examination only. Objective: The study was carried out to see histopathological patterns of uterine and cervical lesions in hysterectomy specimens. Study Design: Histopathology department of Women Medical and Dental College, Abbottabad from August 2021 to August 2022. Materials and Methods: It was a retrospective study done on hysterectomy samples findings in histopathological examination of uterine and cervical area on 80 specimens over a 1 year period. SPSS latest version was used for DATA. Results: 80 patients were included based on histopathological reports of the post hysterectomy specimens. Age of patients lies < 30 years to > 60 years. Majority of the cases were between 41-50 years and 51-60 years of the age while patients between 41-50 years age group were 50 %,adenomyosis (09%), atrophied uterus (5%), Hyperplasia (10%), leiomyoma with adenomyosis (18.5%), Leiomyoma (55%) and leimyosarcoma (2.5%),while cervical pathologies show cervicitis, (62%), cervical dysplasia (21%), cervicitis (papillary) in 07 %, and 10% cases were normal. Different uterine lesions based on the age of the patients show that Leiomyoma is maximally found in patients between 46-60 years and above 60 years of patients and only two cases were marked below 30 Years. Conclusion: The commonest benign lesion was leiomyoma in uterus followed by adenomyosis combined with leiomyoma, while in cervical canal commonest finding was cervicitis in Hysterectomy specimen. Keywords: Adenomyosis, Histopathology, Hysterectomy, Leiomyoma, Cervicitis.